Exploring an adverse effect of social media on adolescent’s mental health - A Halim, Mohd Radzi Tarmizi; Ibrahim, Muhamad Ariff; Nik Mohd Adib, Nik Adlin Nazrin; Hashim, Huzaini; Omar, Rosemaria (IIUM Press, 2023)
Background: Previous studies have reported that adolescent use of social media can have a negative impact on their mental health. In 2021, the National Institutes of Health Malaysia emphasized the urgent need to address digital-related mental health issues, which pose a significant gap in our understanding. Nevertheless, there has been a lack of research on the effects of social media addiction on the mental well-being of local adolescents. This study aims to examine the effect of social media use on mental health issues among adolescents in Kelantan, Malaysia. Methods: A total of 384 respondents voluntarily participated in this cross-sectional study involving ten districts in Kelantan using the snowball sampling method. Results: Analysed data finds social media addiction correlates significantly with depression (r = .390, p < .01), suicide ideation (r = .188, p < .01) and self-esteem (r = .156, p < .01). Multiple regression analysis indicated that suicide ideation was predicted by social media addiction (β = -.01, p < .05) and depression (β - .12, p < .01) but not self-esteem (β = -.002, p > .05). Furthermore, social media moderates the relationship between depression and suicidal ideation (β =.0016, p < .05). Conclusion: Controlling social media use may prevent addiction and promote greater mental health among adolescents.